Respuesta :

Answer:

p is equal to -4

Answer:

p = -4

Step-by-step explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:

5*p-2*p-(-12)=0  

Step  1  :

Pulling out like terms :

1.1     Pull out like factors :

3p + 12  =   3 • (p + 4)  

Step  2  :

Equations which are never true :

2.1      Solve :    3   =  0

A a non-zero constant never equals zero.

Solving a Single Variable Equation :

2.2      Solve  :    p+4 = 0  

 Subtract  4  from both sides of the equation :  

                     p = -4

One solution was found :

                  p = -4

Also to check the work:

5x-4=-20

2x-4=-8

-20 - -8= -12